Violence toward nurses at emergency rooms (ERs) of hospitals of - Moshtaq Eshgh, zahra; Saeedi, maryam; Abed Saeedi, zhila; Alavi Majd, hamid; Najafi Abedi, zahra (Advances in Nursing & Midwifery, 2013)
Abstract Background and Aim ER nurses are at risk of violence due to the nature of their job and confrontation with a variety of patients as well as heavy workload. This can, in turn, leads to decreased quality of care. This descriptive study was conducted to identify prevalence and causes of violence toward nurses at ERs of hospitals affiliated with Medical Universities in Tehran. Methods 100 nurses with at least 1 year continuous experience at ER were included in the study. Data were collected by a questionnaire. The questionnaire contained items including demographics, frequency and characteristics of violence at work (physical, verbal, nonverbal) and the factors involved. Content and test-retest as well as internal consistency (Cronbach’s U) methods were used for Validity and reliability of the questionnaire respectively. Data were analyzed by version 16 of SPSS package. Findings The most frequent type of violence was verbal (87%). The frequencies of nonverbal and physical violence were 70% and 28% respectively. The most common type of verbal violence was yelling (84%) and, in physical violence, it was throwing objects (33%). In nonverbal violence, insulting and threatening look (64%) and hitting on the table were very common. Verbal (48.2%) and nonverbal (65.8%) violence was committed mostly over the past month of the study and at nights. The subjects (38%) experienced verbal violence up to 5 times. The most frequent cause of violence (77%) was the lack of control over entrance of patients’ relatives. chi test showed a significant relationship between physical violence and night shifts (P<0.001) and between female sex of nurses and physical violence (P<0.005). Conclusion ER nurses usually face with violence in a week and the most frequent types are verbal, nonverbal and physical, leading to decreased speed in delivering efficient care to patients and decreased quality of health care resulted from it. Keywords : Violence, Nurse, Emergency rooms (ERs). Corresponding Author : Moshtagh Eshgh Z, Faculty Lecturer, Department of Nursing, Faculty of Nursing and Midwifery, Shahid Beheshti University of Medical Sciences, Tehran, Iran Email: Zmoshtagh@yahoo.com REFERENCES -Adib SM et al (2002). Violence against nurses in health care facilities in Kuwait. International Journal of Nursing Studies. 39 (4) 469-478 -Astrom S et al (2004). Staff’s experience of and the management of violent incidents in elderly care. Scandinavian Journal of Caring Science. 18 (4) 410-416 -Ayranci V (2005). Violence towards health care workers in emergency department in west Turkey. The Journal of Emergency Medicine. 28 (3) 367-365. -Celik SS et al (2007). Verbal and physical abuse against nurses in Turkey.International Nursing Review. 54 (4) 359- 366. -Chen WG et al (2004). Incidence and risk factors of work place violence on nursing staffs caring for chronic psychiatric patients in Taiwan. International Journal Environment Research of Public Health. 6 (11) 2812-2821 -Christopher F et al (1999). Violence in the emergency department-a survey of health care workers. Canadian Medical Association Journal. 167 (70) 1245-1252 -Crilly Y et al (2004). Violence towards emergency department nurses by patients. Accident and Emergency Nursing. 12 (2) 67-73 -Estryn BM et al (2008). Violence risks in nursing- results from the European NEXT study. Occupational Medicine (London). 58 (2) 107-114 -Gacki SJ et al (2009). Violence against nurses working in US emergency departments. Journal of Nursing Administration. 39 (9-8) 340-349 -Gebrerich SG et al (2004). An epidemiological study of magnitude and consequence of work related violence: the Minnesota nurse study. Occupational and Environmental Medicine. 61(6) 495-503. -International Council of Nurses (2006). Abuse and violence against nursing personnel ICN Position Statement. [1 feb 2010] Available at http://www.icn.ch/psviolence00.htm -Kamchuchatt C et al (2008). Work place violence directed at nursing staff at a general hospital in southern Thailand. Journal of Occupational Health. 50 (2) 201-207. -Kwok Rp et al (2006). Prevalence of workplace violence against nurses in Hong Kong. Hong Kong Medical Journal. 12 (1) 6-9. -Labour Office [Home page] 2002 [On line]. Available at: http:/www.ilo.org/publhc/English/dialogue/ector/papers/health/guidelines.pdf> 16 Feb 2010 -Lanza ML et al (2006). Non physical violence: a risk factor for physical violence in health care settings. A A O H N: Official Journal The of American Association of Occupational Health Nurses .54 (9) 397-402 -Lemelin L et al (2004). Workplace violence reported by Canadian nurses. Canadian Journal of Nursing Research. 41(3) 152-167. -Pich J et al (2010) Patient-related violence against emergency department nurses . Nursing and Health Sciences 12( 2), 268–274 hs-525 2274. -Talas M S Kocaöz S Akgüç S (2011). A Survey of violence against staff working in the emergency department in Ankara, Turkey. Asian Nursing Research. 5 (4)197-203. -Uzun O (2003). Perceptions and experiences of nurses in Turkey about verbal abuse in clinical settings. Journal of Nursing Scholarship. 35 (2) 81-85. -Yaghmaei F (2007). [Measuring behavior in research by valid and reliable instruments]. 1 st edition Tehran: Shaheed Beheshti University of Medical Sciences and Health Services publication. (Persian).